Implementation of Indonesia Smart Card Policy in an Effort of Education Equality in Vocational School - Budiman, Indra (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2023)
This study intends to describe the Smart Indonesia Card (KIP) policy’s implementation, beneficiary criteria, implementation strategy, and encouraging and discouraging aspects in an effort to equalize education. This study employs a descriptive qualitative methodology. The employees of the Vocational School of Education at the South Sumatra Province Education Office, the principal and counseling teachers of SMK Kayuagung District, four KIP recipients and their parents, and the principal and counseling teachers of SMK Kayuagung District served as the study’s subjects. The implementation of the Smart Indonesia Card policy in an effort to equalize education in the SMK Kayuagung District is the subject of the study. Through observation, interviews, and documentation, data was gathered. Data triangulation is used to assess the data’s validity. Data analysis techniques included data reduction, data presentation, and conclusion-drawing. According to the findings, the Kayuagung District Vocational School’s KIP targets were pupils who had 470 KIP cards. The outcomes of KIP implementation can aid attempts to promote educational equity.